Making America green and safe : a history of sustainable development and climate change - Hecht, Alan D., 1944- (Cambridge Scholars Publishing, 2018)
Since history is a critical part of future planning, the eight chapters of this book offer both academics and the general public a historical perspective of the evolution of science and policy actions on climate change and steps toward building a resilient and sustainable society, especially at the Environmental Protection Agency (EPA). Reflecting the world today, especially at the EPA, the author, who is a long-time academic and government policy maker and researcher, acknowledges that as David Barry once said (March 22, 1999) ""We live in troubled times, but I feel good about myself, about my